Participatory budgeting to foster inclusivity, transparency and accountability in local government : a case of the City of Ekurhuleni Metropolitan Municipality - Kraai, Sonya Delene (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.